2012
DOI: 10.1007/s40333-013-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in terrestrial surface dry and wet conditions on the Loess Plateau (China) during the last half century

Abstract: This paper, using a revised Penman-Monteith model, computed the terrestrial surface humidity index of the Loess Plateau (China) based on climatic factors of monthly mean temperature, maximum temperature, minimum temperature, relative humidity, precipitation, wind speed and sunshine duration observed on the plateau from 1961 to 2008. The temporal-spatial distribution, anomaly distribution and sub-regional temporal variations of the terrestrial surface dry and wet conditions were analyzed as well. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Moreover, the inner-annual variation of precipitation and temperature was much greater than the inter-annual variation over the 56 years. Similar results were also reported by Yao et al (2013) and and T. . It was also demonstrated that the extent of the detected variations largely depend on the chosen temporal or spatial scales (Western and Blöschl, 1999;Vicente-Serrano et al, 2010).…”
Section: Spatiotemporal Variation Of Climatesupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the inner-annual variation of precipitation and temperature was much greater than the inter-annual variation over the 56 years. Similar results were also reported by Yao et al (2013) and and T. . It was also demonstrated that the extent of the detected variations largely depend on the chosen temporal or spatial scales (Western and Blöschl, 1999;Vicente-Serrano et al, 2010).…”
Section: Spatiotemporal Variation Of Climatesupporting
confidence: 91%
“…It starts from the TaiHang Mountains in the east, reaches the RiYue Mountain in the west, and borders on the QinLing Mountains in the south and Yin Mountain in the north. The region lies in the marginal zone of the East Asian and South Asian summer monsoon and thus is sensitive to the activity and intensity of the monsoon (Yao et al, 2013). The annual precipitation ranges from 150 mm in the northwest to 800 mm in the southeast, 55-78% of which falls from June to September in the form of high-intensity storms.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…In China's dryland region, various changes have been observed in temperature, precipitation and other climatic factors during the past decades (Fan et al, 2012;Ge et al, 2013;Meng et al, 2013;Wang et al, 2006;Zhao, 2013). Many studies analyzed the effect of recent climate changes on droughts (Yao et al, 2013), stream runoff Zhang et al, 2013), plant phonological development (Dai et al, 2012(Dai et al, , 2014Ge et al, 2013), and plant productivity (He et al, 2014;Xiao et al, 2013;Yao et al, 2012) in parts of the region. Some studies analyzed changes in rainfall erosivity, indicating that the rainfall erosivity tended to increase in north Xinjiang and north Tibet Plateau, but to decrease in the Loess Plateau (Liu et al, 2013;Xin et al, 2011;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%